The Sound of Revolution: BBC Monitoring and the Hungarian uprising, 1956. Issue 4 (2nd October 2019) - Webb, Alban
Abstract : Radio played a vitally important role during the 1956 Hungarian uprising: as an information service, diplomatic interlocutor and cultural mediator. Broadcasters and the authorities that stood behind them on both sides of the Iron Curtain mapped, interpreted and, at times, appeared to influence the course of events on the ground. The BBC Monitoring Service Transcription Collection offers an essential and unexplored perspective on the mediated experience of the Hungarian uprising, in the context of the wider political warfare battle of the cold war.